Kesan berat beg galas terhadap corak berjalan kanak-kanak sekolah di Malaysia: satu kajian awal - Azmin Sham Rambely,; Tan, Tzuen Poh; Noorhaslinda Hasan,; Rohan Ganason, (Penerbit ukm, 2007)

(untitled)
The objective of the study was to investigate the effects of varying backpack loads carriage on gait patterns and kinematics parameters for Malaysian school children while level walking. Two subjects were chosen and asked to walk on a track about 8 meters long for few times at their natural cadence for four complete cycles, each with loads 0, 10%, and 20% of their body weights. The walking activity was recorded using the Motion Analysis System with six infrared and high speed cameras at 200 Hz. The results showed that there were significant differences in stance duration, double leg support duration, swing duration, stride length, and step length between the loads of 0%, 10% and 20% of body weight